ANALYSIS OF EDUCATION POLICIES RELATED TO IMPROVING TEACHER PERFORMANCE - Badrudin, Badrudin; Munaya, Amira; Indayanti, Aneu Nandya; Mubasysyir, Azhar; Ayustina, Dina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Teachers play an important role in carrying out functions and realizing national education because teachers are educators who will produce quality students by providing knowledge to students. To help teachers meet these expectations, it is necessary to have efforts that can be taken in improving teacher performance in order to achieve quality education and produce quality students. This study aims to analyze educational policies related to improving teacher performance. The research method used in this study is a qualitative method with a descriptive approach to the study of documents / texts